Comparative features of bioelements content in blood, liver and bone tissues in a rat model of crush-syndrome (Bangladesh Journal of Medical Science, 2024)
Objective: Crush  syndrome  (CS)  remains  a  life-threatening  condition. This  research  aims  to  investigate the  changes  of  the  macro-  and microelement content in blood, liver and bone tissue in a rat model of CS.Methods  Studies were conducted on 40 nonlinear mature white male rats. The left  hind  limb  of  the  rat  was  subjected  to  the  mechanical  pressure for  4  hours.  The  compressed  area  was  4  cm   with  a  compressive  2 2 force  of  4.25  kg/cm .  Determination  of  total  calcium,  magnesium  and inorganic phosphate contents in blood serum was performed on a  semi-automatic  biochemical  analyser  Humalyzer  2000  (Human, Germany)  using  standard  reagent  kits.  The  content  of  calcium, magnesium,  copper  and  zinc  in  the  liver  and  bone  tissue  was determined by atomic absorption spectrometry on a Selmi C-115 M spectrophotometer.Results: It was found that serum content of calcium decreased on the 1st day  of  observation  (by  10.1%),  but  increased  on  the  14th  day  (by 23.0%);  the  magnesium  content  progressively  decreased  during postcompression  period,  and  the  content  of  inorganic  phosphate increased on the 14th day of observation by 36.6% (p